CD5-Positive Primary Cutaneous Diffuse Large B-Cell Lymphoma-Leg Type - Alexandra Papoudou-Bai; Leonidas Marinos; Amalia Vassou; Eleni Kapsali; Panagiotis Kanavaros (Case Reports in Dermatological Medicine)
Most primary cutaneous B-cell lymphomas (PCBCL) are CD5 negative, and only a few cases were found to express CD5. We report the first well-documented CD5+ primary cutaneous diffuse large B-cell lymphoma-leg type (PCDLBCL-LT). A 71-year-old woman with a history of Multiple Sclerosis was admitted because of a nodule at the left thigh. Histological examination of the skin biopsy disclosed a diffuse dermal infiltration by large lymphoid cells. Immunohistochemistry revealed that these large cells were positive for CD5, CD20, CD79a, MUM1/IRF4, Bcl6, Bcl2, and cytoplasmic IgM/λ, whereas CD3, CD56, CD23, CD21, CD10, CD30, cyclin D1, CD68, lysozyme, myeloperoxidase, and CD34 were not detected. Thus, the diagnosis of a CD5+ PCDLBCL-LT was made. Despite treatment, the patient died 11 months after initial diagnosis.